2014
DOI: 10.1503/cmaj.131064
|View full text |Cite
|
Sign up to set email alerts
|

Postmenopausal hormone replacement therapy and risk of acute pancreatitis: a prospective cohort study

Abstract: Interpretation: Use of postmenopausal hormone replacement therapy was associated with increased risk of acute pancreatitis. Physicians should consider this potential increase in risk when prescribing such therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Finally, we observed an association of HRT use with both AP and CP, which is in agreement with other studies 39,40 . A prospective study of over 31,000 Swedish women reported that women who had ever used HRT had a 57% greater risk of developing AP than never users; the risk did not differ significantly between present and former use 39 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Finally, we observed an association of HRT use with both AP and CP, which is in agreement with other studies 39,40 . A prospective study of over 31,000 Swedish women reported that women who had ever used HRT had a 57% greater risk of developing AP than never users; the risk did not differ significantly between present and former use 39 .…”
Section: Discussionsupporting
confidence: 93%
“…A prospective study of over 31,000 Swedish women reported that women who had ever used HRT had a 57% greater risk of developing AP than never users; the risk did not differ significantly between present and former use 39 . Given that a substantial proportion of women in the U.S. report HRT use (38.5% in the IWHS), it is important to further evaluate this association.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast to the sparse data on polypharmacy per se, the use of specific drugs has received more systematic study in relation to risk of acute pancreatitis. As an example, our group has found positive associations with tetracycline, antidopaminergic drugs, selective serotonin reuptake inhibitors, oral glucocorticoids, and postmenopausal hormone replacement therapy . Other research has at the same time indicated that comorbid conditions can cause acute pancreatitis, such as cardiovascular disease and diabetes .…”
Section: Discussionmentioning
confidence: 94%
“…As an example, our group has found positive associations with tetracycline, 6 antidopaminergic drugs, 9 selective serotonin reuptake inhibitors, 10 oral glucocorticoids, 11 and postmenopausal hormone replacement therapy. 12 Other research has at the same time indicated that comorbid conditions can cause acute pancreatitis, such as cardiovascular disease 13 and diabetes. 14 However, as shown with the case of diabetes, it can be difficult to disentangle the effect of the comorbid condition from the effect of the drug treatment for that condition.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis has been described in subjects using oral contraceptives, IVF-patients without using estrogen, and there is a report of increase risk of acute pancreatitis in postmenopausal women using hormone therapy [ 2 3 4 ]. Here we report a case of estrogen-induced acute pancreatitis in which estrogen was administered for the cryo-thaw ET.…”
Section: Discussionmentioning
confidence: 99%